Phospholipase A2 Receptor Antibodies and Clinical Prognosis in Patients with Idiopathic Membranous Nephropathy: An Updated Systematic Review and Meta-Analysis - Jialing Zhang; Zhengjia Fan; Peixin Wang; Ai-Hua Zhang (Karger Publishers, 2023)
Background: Idiopathic membranous nephropathy (IMN) is the most common form of primary nephrotic syndrome in adults. Antibodies against the M-type phospholipase A2 receptor (PLA2R-ab) are considered as diagnostic biomarkers of IMN. Objective: Here, we performed an updated meta-analysis to assess the diagnostic value of PLA2R-ab for clinical remission in IMN patients. Method: PubMed, Embase, and Cochrane databases were searched for relevant studies published before September 2022. Odds ratios and corresponding 95% confidence intervals were determined using a fixed or random effects model. The heterogeneity among studies was explored by subgroup analysis. Results: Sixteen studies involving 1,761 IMN participants were included. There were significant differences between PLA2R-ab (+) and PLA2R-ab (−) patients in terms of complete remission (CR) and spontaneous remission. The rates of partial remission (PR) and relapse were similar between the two groups. Patients with PLA2R-ab (−) were at a higher CR rate when treated with a calcineurin inhibitor or a treatment course for 3 months and 6 months, while the spontaneous remission rate was higher in PLA2R-ab seronegative patients from Asia. However, the CR and spontaneous remission rate only significantly declined in IMN patients with the highest titer, but not a middle titer, when compared to those with the lowest titer. Conclusion: In contrast with previous meta-analyses, our results verified that PLA2R-ab can likely predict CR and spontaneous remission in IMN patients, instead of PR and relapse. Race, immunosuppressive agents, and duration of treatment may affect the prognostic value of PLA2R-ab. Considering that the remission rate of IMN patients with a middle level of PLA2R-ab was not different from that of patients with the lowest level, a proper cut-off value of PLA2R-ab for prognosis should be clarified.